Kecenderungan Mahasiswa Pendidikan Biologi Fkip Ums Dalam Melaksanakan Penelitian Skripsitahun 2015 - Nugroho, Rio Taufiq (2016)
Credible research paper is a task that must be taken by students after taking all or most subjects, as a condition to obtain a Bachelor's degree.The purpose of this study was to determine the tendency of Biology Education Student this UMS in conducting research paper in 2015. The method of the research is qualitative descriptive using paper documentation. This research is using model survey strategy to obtain and disclose the data, so the result may generalize a phenomenon that is happening. Data analysis used qualitative descriptive. Based on the results of the study, the selected areas of research students are applied (53.2%), education (30.8%), and pure (16.0%).The selected student research approach is qualitative (47.4%), quantitative (28.2%), as well as the combination (24.4%). The research method selected students experiment (67.9%), descriptive (25.6%), exploration (3.8%), as well as an explanatory, R&D, PTK and library research 0.6% respectively. Study schools are being focused in educational research, junior high school (83,3%), senior high school (10,4%), university (4,2%) and others( 2,1%).Thus, it can be concluded that the students of Biology Education FKIP UMS who graduated in 2015 had a tendency to choose the field of applied research, qualitative research approach, the experimental method, as well as the junior high school level(83,3%) are being focused in educational research. Keywords:trends, research paper, biology education, qualitative descriptive.